Use of the thermo-hydraulic system code RELAP5/MOD3.2 to transient analysis events of the VR-1 reactor - Jakub Mátl; Filip Fejt (Acta Polytechnica)
The article explores the application of the RELAP5 thermo-hydraulic code for transient simulations on the VR-1 research reactor, focusing on reactor vessel nodalisation and coolant stratification above the core. The study investigates Reactivity-Initiated Accidents (RIAs) at the VR-1 reactor, triggered by various initiating events such as inadvertent control rod withdrawal or experimental channel flooding. By comparing several nodalisation models for protected and unprotected RIAs, the study discusses the impact of the nodalisation approach. Key findings highlight the significant influence of user effects and reactor vessel nodalisation on the accuracy and reliability of these predictions. The article also examines two-phase flow flashing instability and the reactor SCRAM delay effect. The conclusions drawn from different nodalisation approaches may offer insights into optimising research reactor safety analysis and the simulation of natural circulation systems.